1978
DOI: 10.1007/bf00052447
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and patterns of help-seeking

Abstract: This study reconstructs and analyzes pathways of help-seeking traveled by severely disabled mental patients in the community. Ethnicity is a prime factor in differentiating patterns of help-seeking in that Chinese patients are kept for prolonged periods of time within their families in the beginning of pathways, while Anglo-Saxons and Middle Europeans are referred by their families or themselves to multiple social and mental health agencies. Native Indians are referred by persons other than family members or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 5 publications
7
65
1
2
Order By: Relevance
“…Spouses who expressed fear of the stigma were more likely to rely upon professionals to decide on hospitalization for the patient. Lin et al (1978) confirm these findings for the Chinese. In studying referrals to a community mental health team, the researchers found Chinese families attended to the patient for a prolonged period.…”
Section: Discussionsupporting
confidence: 76%
“…Spouses who expressed fear of the stigma were more likely to rely upon professionals to decide on hospitalization for the patient. Lin et al (1978) confirm these findings for the Chinese. In studying referrals to a community mental health team, the researchers found Chinese families attended to the patient for a prolonged period.…”
Section: Discussionsupporting
confidence: 76%
“…Help-seeking behaviour has been found to differ between families of different cultural backgrounds [46][47][48] . However, it has been pointed out that many individuals can hold parallel health belief models.…”
Section: Family Influences On Religious Symbolsmentioning
confidence: 99%
“…While the rarity of incident cases makes community surveys impractical, counts based on treatment statistics may be inadequate because certain casesperhaps the least severe, or those from cultural groups known for their reluctance to surrender a sick family member to the mental health care system -may never seek treatment. Lin and his colleagues in Vancouver (36) found that, on the whole, Chinese schizophrenics came to the attention of the mental health treatment system later in their illness than their Caucasian or Native Indian counterparts. If there is a delay before seeking treatment it is possible that patients may no longer qualify as incident cases by the time their disorders are identified.…”
Section: Rates and Risk Factorsmentioning
confidence: 99%
“…If not entirely different illnesses, there may be a different preponderance of one sub-type of illness in Asians as compared to Caucasians, which, in tum, may help account for the differential response to neuroleptics. Studies by Lin and colleagues (36) and by Katz (134) suggest that Asian families are more tolerant of symptoms such as helplessness and lack of initiative than Caucasian families. Asian families tend to protect psychotic family members, seeking help only when behaviour becomes threatening or dangerous.…”
Section: Proposals For Future Researchmentioning
confidence: 99%